Kajian Sifat Fisikokimia dan Komposisi Asam Lemak Minyak Kernel Biji Mangga - Fajriyati Mas’ud (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2022)
Mango seed kernel contain high quality oil, the oil is composed by high quality fatty acids and contains large amounts of polyphenols. This study aims to examine the physicochemical properties and fatty acid composition of the kernel seed oil of golek mango, manalagi mango, and bacang mango. The oil was extracted by maceration method using ethanol for 48 h, and physicochemical properties, fatty acid composition, and polyphenol content were analyzed. The results showed that the physicochemical properties of oil were within the range of values suitable for consumption. The oils contain high concentration of oleic acid and polyphenols, as well as quite high levels of stearic acids. The results of this study support the potential for developing the oils as a raw material for spreads products and as a functional food.